Efficiency of plant origin drugs in gastrointestinal bleeding ulcer genesis treatment = Ефективність застосування лікарського засобу рослинного походження для лікування шлунково-кишкових кровотеч виразкового генезу = Эффективность применения лекарственных средств растительного происхождения для лечения желудочно-кишечных кровотечений язвенного генеза - I. V. Savytskiy; M. O. Ostapets; S. G. Znamerovskiy (Kazimierz Wielki University, 2017)
Savytskiy I. V., Ostapets M. O., Znamerovskiy S. G. Efficiency of plant origin drugs in gastrointestinal bleeding ulcer genesis treatment = Ефективність застосування лікарського засобу рослинного походження для лікування шлунково-кишкових кровотеч виразкового генезу = Эффективность применения лекарственных средств растительного происхождения для лечения желудочно-кишечных кровотечений язвенного генеза. Journal of Education, Health and Sport. 2016;6(11):640-648. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.204936 http://ojs.ukw.edu.pl/index.php/johs/article/view/4072         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016.   УДК 616.15-008.1:34-005.1;615.322   ЕФЕКТИВНІСТЬ ЗАСТОСУВАННЯ ЛІКАРСЬКОГО ЗАСОБУ РОСЛИННОГО ПОХОДЖЕННЯ ДЛЯ ЛІКУВАННЯ ШЛУНКОВО-КИШКОВИХ КРОВОТЕЧ ВИРАЗКОВОГО ГЕНЕЗУ   І. В. Савицький1, М. О. Остапець2, С. Г. Знамеровський1   1Одеський національний медичний університет, Одеса, Україна 2Національний фармацевтичний університет, Харків, Україна   marina.ostapets.22@mail.ru               Реферат Стаття присвячена вивченню впливу біологічно активних речовин родовика лікарського на систему гемостазу та можливість його застосування з метою лікування та профілактики шлунково-кишкових кровотеч виразкового генезу. На моделі спиртово-преднізолонової виразки шлунку встановлено, що досліджуваний екстракт проявив виражений гемостатичний ефект відносно контрольної патології (неліковані тварини) та порівняно з референс-препаратом. Підтвердженням даної активності слугували показники вмісту азоту сечовини в сироватці крові та позитивний тест на приховану кров в калі. Одержані результати можна пояснити фітохімічним складом досліджуваного екстракту - поліфеноли (фенільні сполуки з великою кількістю гідроксилів) здатні утворювати зв'язки за донорно-акцепторним механізмом з гідроксилами плазмових факторів зсідання крові, таким чином вони впливають на коагуляційну фазу системи гемостазу. Ключові слова: шлунково-кишкові кровотечі, родовик лікарський, гемостаз, виразка шлунку.   efficiency of plant origin drugs in gastrointestinal bleeding ulcer genesis treatment   I. V. Savytskiy, M. O. Ostapets, S. G. Znamerovskiy   Odessa national medical university National University of Pharmacy Abstract This article is dedicated to the influence of bio-active substances of Sanguisorba officinalis on hemostatic system and the possibility of its use in the treatment and prevention of ulcer genesis gastrointestinal bleeding. During the alcohol-prednisolone model experimental study of gastric ulcers the analyzed extract showed notable hemostatic effect comparatively with the control pathology (without treatment) and with the reference drug. This influence was indicated by the content of urea nitrogen in the blood and serum positive test for occult blood in the feces. The results can be explained by the composition of the researched extract: high levels of polyphenols were observed. Polyphenols (phenyl compounds with a large number of hydroxyl groups) are capable to form a donor-acceptor mechanism based connection with hydroxyl groups of plasma coagulation factors, thus, they affect the coagulation phase of the hemostatic system. Key words: gastrointestinal bleeding, Sanguisorba officinalis ,hemostatic effect, gastric ulcer.    ЭФФЕКТИВНОСТЬ ПРИМЕНЕНИЯ ЛЕКАРСТВЕННЫХ СРЕДСТВ РАСТИТЕЛЬНОГО ПРОИСХОЖДЕНИЯ ДЛЯ ЛЕЧЕНИЯ ЖЕЛУДОЧНО-КИШЕЧНЫХ КРОВОТЕЧЕНИЙ ЯЗВЕННОГО ГЕНЕЗА     И. В. Савицкий1, М. А. Остапец2, С. Г. Знамеровский1   1Одесский национальный медицинский университет 2 Национальный фармацевтический университет   Реферат Статья посвящена изучению влияния биологически активных веществ кровохлебки лекарственной на систему гемостаза и возможность ее применения с целью лечения и профилактики желудочно-кишечных кровотечений язвенного генеза. На модели спиртово-преднизолоновой язвы желудка установлено, что исследуемый экстракт проявил выраженный гемостатический эффект относительно контрольной патологии (без лечения) и в сравнении с референс-препаратом. Подтверждением данной активности служили показатели содержания азота мочевины в сыворотке крови и положительный тест на скрытую кровь в кале. Полученные результаты можно объяснить фитохимическим составом исследуемого экстракта - полифенолы (фенильные соединения с большим количеством гидроксилов) способны образовывать связи по донорно-акцепторному механизму с гидроксилами плазменных факторов свертывания крови, таким образом они влияют на коагуляционную фазу системы гемостаза. Ключевые слова: желудочно-кишечные кровотечения, кровохлебка лекарственная, гемостаз, язва желудка.